1995
DOI: 10.1111/j.1469-0691.1995.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of SCH 27899, Oligosaccharide Member of the Everninomycin Class with a Wide Gram-Positive Spectrum

Abstract: The in vitro antimicrobial activity of SCH 27899 (everninomycin), a novel oligosaccharide compound of the everninomycin class, was compared with vancomycin, chloramphenicol, clinafloxacin, teicoplanin and doxycycline against 428 clinical strains of bacteria. Everninomycin base exhibited the greatest antimicrobial activity compared to other formulations against all strains tested (MIC90: 0.25 microg/ml) followed by clinafloxacin and teicoplanin (MIC90: 0.5 microg/ml), vancomycin (MIC90: 2 microg/ml), and doxycy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
19
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 10 publications
4
19
0
Order By: Relevance
“…Killing curve data suggested that evernimicin is not uniformly bactericidal (9). We used a misincorporation assay to determine if evernimicin, like streptomycin, exerts its limited bactericidal effects through promotion of misreading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Killing curve data suggested that evernimicin is not uniformly bactericidal (9). We used a misincorporation assay to determine if evernimicin, like streptomycin, exerts its limited bactericidal effects through promotion of misreading.…”
Section: Discussionmentioning
confidence: 99%
“…One potential new agent is evernimicin (SCH 27899), a member of the everninomicin class of antibiotics isolated from Micromonospora carbonaceae (5)(6)(7). Evernimicin is an oligosaccharide antibiotic with activity against a broad range of gram-positive pathogenic bacteria including glycopeptide-resistant enterococci, methicillin-resistant staphylococci, and penicillin-resistant streptococci (9). However, the mode of action of evernimicin is unclear.…”
mentioning
confidence: 99%
“…Evernimicin (SCH 27899) is a novel oligosaccharide antibiotic (8,22) with activity against a broad range of gram-positive pathogenic bacteria including glycopeptide-resistant enterococci, methicillin-resistant staphylococci, and penicillin-resistant streptococci (11). We previously demonstrated that evernimicin inhibits protein synthesis in Staphylococcus aureus and in a susceptible Escherichia coli strain (13).…”
mentioning
confidence: 99%
“…Several new drugs targeted against the ribosome are currently being developed, including the oxazolidinones (3,18). After first being identified as prospective antimicrobial agents in 1987 (32), oxazolidinones were abandoned for some time due to their high toxicity.…”
mentioning
confidence: 99%